Construction and Validation of a Mutation-Related Model in Papillary Renal Cell Carcinoma and Associated Immune Infiltration - Xiangyun Li; Yang Liu; Luting Zhou; Jianhua Wang; Xiaoqun Yang (Karger Publishers, 2024)
Background: To improve the clinical evaluation of the prognosis of papillary renal cell carcinoma (PRCC), we screened a model to predict the survival of patients with mutations in related genes. Methods: We downloaded RNA sequencing information from all patients with PRCC in TCGA. We first analyzed the differences in genes and the enrichment of these differences. Then, by selecting mutant genes, constructing a protein-protein interaction network, least absolute shrinkage and selection operator regression, and multivariable Cox regression, a prognosis model was constructed. Additionally, the model was validated using external data sets. We analyzed the immune infiltration of PRCC and the correlation between the model and popular targets. Finally, we performed tissue microarray analysis and immunohistochemistry to verify the expression levels of the three genes. Results: We constructed a three-gene (never in mitosis gene A-related kinase 2 [NEK2], centromere protein A [CENPA], and GINS complex subunit 2 [GINS2]) model. The verification results indicated that the model had a good prediction effect. We also developed a visual nomogram. Enrichment analysis revealed the major pathways involved in muscle system processes. Immunoassays showed that the expression level of CENPA was positively correlated with PD-1 and CTLA4 expression levels. Immunohistochemical and tissue microarray results showed that these three genes were highly expressed in PRCC, which was consistent with the predicted results in the database. Conclusion: We constructed and verified a three-gene model to predict the patient survival. The results show that the model has a good prediction effect.